What’s the Difference? Kant and Lacan - Hajdini, Simon (Filozofski vestnik, 2016)
In line with the aim of this issue of Filozofski vestnik, which proposes to rethink the importance of Kantian philosophy for contemporary debates on the concepts of the subject and the object, I attempt to develop the consequences of one of Kant’s “conceptual monsters”, namely that of transcendental reflection. Initially, I will follow Kant’s line of thought, which – however – will immanently lead to a certain theoretical deadlock, or “contradiction”, which in turn will open up the possibility of a passage from (Kantian) reflection to (Hegelian-Lacanian) speculation, and thus also to a notion of the subject that is at odds with Kant’s argument but comes to light the moment we push the argument to the extreme of its consequences.